2015
DOI: 10.1038/ncomms9366
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the transport history of pebbles on Mars

Abstract: The discovery of remarkably rounded pebbles by the rover Curiosity, within an exhumed alluvial fan complex in Gale Crater, presents some of the most compelling evidence yet for sustained fluvial activity on Mars. While rounding is known to result from abrasion by inter-particle collisions, geologic interpretations of sediment shape have been qualitative. Here we show how quantitative information on the transport distance of river pebbles can be extracted from their shape alone, using a combination of theory, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 38 publications
4
110
0
Order By: Relevance
“…The underlying conglomerates of the Liga and Point_Coulomb members are also interpreted as being formed by migrating subaqueous bed forms or barforms in a fluvial environment, similar to the interpretation of conglomerates observed early in Curiosity's mission prior Yellowknife Bay [ Williams et al ., ]. The rounding of clasts within the conglomerates suggests transport distances of tens of kilometers [ Szabó et al ., ], which is consistent with deposition in an alluvial fan environment and transport from Gale crater's northern rim (section 4).…”
Section: Stratigraphy and Depositional Environments At The Kimberleysupporting
confidence: 79%
“…The underlying conglomerates of the Liga and Point_Coulomb members are also interpreted as being formed by migrating subaqueous bed forms or barforms in a fluvial environment, similar to the interpretation of conglomerates observed early in Curiosity's mission prior Yellowknife Bay [ Williams et al ., ]. The rounding of clasts within the conglomerates suggests transport distances of tens of kilometers [ Szabó et al ., ], which is consistent with deposition in an alluvial fan environment and transport from Gale crater's northern rim (section 4).…”
Section: Stratigraphy and Depositional Environments At The Kimberleysupporting
confidence: 79%
“…Likewise, a glacial origin is discounted due to the lack of large boulders as well as striated pebbles usually typical of moraines [e.g., Leeder , ]. Based on their rounding, Szabo et al [] showed that the clasts of some of the conglomerate studied here are interpreted to have been carried tens of kilometers from their source, by bed load transport on an alluvial fan. This is consistent with an origin for the clasts within the conglomerates as being from the rim and wall of Gale Crater [ Palucis et al , ; Grotzinger et al , ].…”
Section: Geological Observationsmentioning
confidence: 96%
“…Finegrained sediments are most readily formed by downstream fining in alluvial settings, and evidence for this is preserved in the Gale crater moat (74). The even and fine lamination observed in the Murray formation at Marias Pass is inconsistent with direct fallout of distal volcanic ash, even through a water column (1).…”
Section: Significance Of Tridymite In the Murray Formationmentioning
confidence: 97%